Temperature switch of electrochemical Seebeck coefficient of Fe2+/Fe3+via formation of [FeCl4]2−/[FeCl4]−. Issue 6 (27th January 2023) - Nomura, Yunika; Inoue, Dai; Moritomo, Yutaka
Abstract : Temperature change switches the electrochemical Seebeck coefficient ( α ) of Fe 2+ /Fe 3+ via transformation of the electrochemically-active redox pair. Abstract : The electrochemical Seebeck coefficient ( α = d V /d T ; V and T are the redox potential and temperature, respectively) is important parameter for thermoelectric conversion. Here, we found that α of Fe 2+ /Fe 3+ in dimethyl sulfoxide (DMSO) with small amount of 19 M LiCl aqueous solution exhibits a crossover behavior from 1.4 mV K −1 (20 °C ≤ T ≤ 40 °C) to ≈0 mV K −1 (50 °C ≤ T ≤ 80 °C). The molar absorption ( ε ) spectra revealed that the crossover is ascribed to the transformation of the dominant Fe 3+ complex from [FeL6 ] 3+ (L is solvent molecule) to [FeCl4 ] − .